Gene therapy: evidence, value and affordability in the US health care system. (January 2018) - Hampson, Grace; Towse, Adrian; Pearson, Steven D; Dreitlein, William B; Henshall, Chris
Aims: To explore the challenges presented by gene therapies, discuss potential solutions, and present policy recommendations.Methods: A review of the literature and series of expert interviews were conducted and discussed at a Policy Forum convened by The Institute for Clinical and Economic Review (ICER). The Policy Forum was attended by independent experts and senior representatives from 20 payer organizations and life sciences companies.Results: Three categories of challenges are identified: evidence generation, assessing value and affordability. Possible solutions and policy recommendations are presented for each of the three main categories of challenges.Conclusions: Gene therapies present exciting opportunities, but also pose major challenges. Dialogue between manufacturers and payers around the issues and possible solutions is crucial.